If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -7 = 24x + 2 Reorder the terms: -7 + 12x = 24x + 2 Reorder the terms: -7 + 12x = 2 + 24x Solving -7 + 12x = 2 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. -7 + 12x + -24x = 2 + 24x + -24x Combine like terms: 12x + -24x = -12x -7 + -12x = 2 + 24x + -24x Combine like terms: 24x + -24x = 0 -7 + -12x = 2 + 0 -7 + -12x = 2 Add '7' to each side of the equation. -7 + 7 + -12x = 2 + 7 Combine like terms: -7 + 7 = 0 0 + -12x = 2 + 7 -12x = 2 + 7 Combine like terms: 2 + 7 = 9 -12x = 9 Divide each side by '-12'. x = -0.75 Simplifying x = -0.75
| 2*56=-4 | | 2/5(25)-8=1/5(25)+7 | | 120w-23w=691 | | 1.25-0.3k+.5=1.3+0.5k | | 12x=11x-23 | | P-4+6+7p=74 | | 120w+23w=691 | | (-4-7)+1= | | b/13-3b/13=8/3 | | -16+18=-2(x+6) | | -4=-1-3 | | .5(4x+14)=2(2x-7) | | 125c^2-180= | | .4y+6=31 | | 0.5x-0.75y=-2 | | 9=6(x+6)-7x | | h=160t-16t^2 | | -22-7x=48 | | 4(x-1)-4=2x+2(-3+x) | | u/4=-8 | | 9-0.7k=9 | | 2.37=.87h-.25 | | -5(6+5p)=136 | | -9x-36=90 | | 1+x+7-9x=-24 | | 16x-2=40x+16 | | 22=13+x | | 8a+3(-7)=3 | | -2b/13=8/3 | | a^12=5 | | 54+8x=158 | | (3x+8)=5x |